Validation of a GC-MS method for the simultaneous determination of five coumarins derivatives in natural soil samples - Oliveros-Bastidas, Alberto; de Almeida Barbosa, Luiz Claudio; Demuner, Antonio (Ciencia, 2016)
1,2-Benzopyrones are secondary metabolites are widely distributed in plants. As these compounds potentially migrate into the soil, their mineralization kinetics, chemical transformation and concentration are important to define their toxic potential. However, despite the various analytical techniques available for the determination of xenobiotics in soil, there are no validated methods for the extraction and determination of coumarins in soil.It was therefore deemed of interest to develop a method for their extraction and quantification. The GC-MSbased method reported herein was validated with external calibration for the simultaneous determination of 5 coumarins in soil samples. After testing various solvent systems, ethanol: acetone (1:1, v/v) was found to be the most effective. Recoveries of coumarin ranged from 77% to 97%, with a variation coefficient smaller than 3.55 and limits of detection at 0.6, 0.5, 2.7, 1.2 and 1.2 mg kg-1 soil for compounds 1-5, respectively, were obtained. Matrix interferences do not show effects in the determinations.